Morphological and cultural characteristics of pathogens isolates Septoria nodorum and Septoria tritici in Kazakhstan (Experimental biology, 2015)
Studied morphological and cultural characteristics of isolates of the fungus Septoria spp. isolated from different wheat varieties and regions of Kazakhstan. In 2012-2013 were obtained 41 isolate pathogens Septoria, 23 isolates are S. tritici and 18 - S. nodorum, respectively. In the study of morphological and cultural properties identified nine morphotypes of S. tritici and six morphotypes of S. nodorum. All studied isolates of the fungus Septoria was characterized by average spirulina ability. Among the selected isolates of the fungus Septoria spp. in populations dominated 6 types of colonies.
Keywords: wheat; Septoria nodorum; Septoria tritici; morfotype; isolate